2021
DOI: 10.3390/su13168841
|View full text |Cite
|
Sign up to set email alerts
|

Can Malaysia’s National Affordable Housing Policy Guarantee Housing Affordability of Low-Income Households?

Abstract: Housing affordability is a long-held issue in Malaysia, and housing policies have been implemented for low-income households over the years. However, there is a contradiction that housing affordability of low-income households has not been met, while the bulk of affordable housing is still vacant. In 2019, Malaysia enacted the National Affordable Housing Policy (DRMM) which was intended to improve housing affordability for low-income groups. This paper aims to answer why Malaysia’s long-term implementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…The funding strategical theme is also aimed at improving low earners' access to finance, which can help to improve housing financing capability. This assertion is congruent with Liu and Ong's study [84], which found that employing various housing financing models can help improve home financing. For example, the implementation of the funding strategical theme as a strategy was aimed at bringing together cooperatives and housing associations to access funds through the Federal Mortgage Bank of Nigeria and the Nigeria Mortgage Refinance Company (NMRC), with measures to promote long-term sustainable and inexpensive funding options for the housing sector.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The funding strategical theme is also aimed at improving low earners' access to finance, which can help to improve housing financing capability. This assertion is congruent with Liu and Ong's study [84], which found that employing various housing financing models can help improve home financing. For example, the implementation of the funding strategical theme as a strategy was aimed at bringing together cooperatives and housing associations to access funds through the Federal Mortgage Bank of Nigeria and the Nigeria Mortgage Refinance Company (NMRC), with measures to promote long-term sustainable and inexpensive funding options for the housing sector.…”
Section: Discussionsupporting
confidence: 84%
“…An adjustment of land prices through an effective approach is required to ensure land supply for housing development as well as to improve housing affordability [84,86]. The lack of access to land stands as a vital challenge to housing development for lowincome earners, as land is seen as an asset in housing development.…”
Section: Discussionmentioning
confidence: 99%
“…The house prices according to NAPIC (2020) still seriously unaffordable therefore the quantities of unsold housing units remain huge. This is consistent with the study by Liu and Ong (2021). Although there are a significant number of unsold houses, a considerable number of middle-income households are still looking for reasonably priced and affordable houses to buy.…”
Section: Research Backgroundsupporting
confidence: 91%
“…Delaying the purchase of a house makes people lose the opportunity to be able to buy a house and then from time to time due to inflation, their purchasing power decreases with house prices increasing. Thus, the priority of housing must start from improving the demand side to ensure that low-income people can actually have an effective purchasing power for the provision of houses (Juniarko et al, 2012;Liu & Ong, 2021). Therefore, government intervention in the form of subsidized Home Ownership Credit (KPR) using a housing finance assistance scheme is expected to be able to help people get the houses they need and live a more decent life.…”
Section: Introductionmentioning
confidence: 99%